2019
DOI: 10.1093/rb/rbz009
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodeling effect of a chitosan and calcium phosphate-based composite

Abstract: Chitosan is a biocompatible polymer that has been widely studied for tissue engineering purposes. The aim of this research was to assess bone regenerative properties of an injectable chitosan and calcium phosphate-based composite and identify optimal degree of deacetylation (%DDA) of the chitosan polymer. Drill holes were generated on the left side of a mandible in Sprague-Dawley rats, and the hole was either left empty or filled with the implant. The animals were sacrificed at several time points after surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Because of its osteoconductive properties and structural homology to proteoglycans of extracellular matrices, chitosan has been proposed as a coating in bone implants or a component in composite materials [ 7 ]. So far, experimental studies have reported that alloy surfaces, layer assembly, and the degree of deacetylation n chitosan affect the promotion of osseointegration, bone remodeling, and delivery of growth factors at the implant-tissue interface [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its osteoconductive properties and structural homology to proteoglycans of extracellular matrices, chitosan has been proposed as a coating in bone implants or a component in composite materials [ 7 ]. So far, experimental studies have reported that alloy surfaces, layer assembly, and the degree of deacetylation n chitosan affect the promotion of osseointegration, bone remodeling, and delivery of growth factors at the implant-tissue interface [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained here can be viewed in the light of results from experiments that our group performed in rat mandibular bone [17]. It was found that implants containing 50-70% DDA chitosan polymer may stimulate new bone growth.…”
Section: Discussionmentioning
confidence: 74%
“…In a previous study in a rat model the quantitative assessment of osteogenic effect of chitin derivatives was established and used to compare the osteogenic effect of deacetylated chitin derivatives, with degree of deacetylation from 50-96% [17]. The study showed that injectable implants containing 50% and 70% deacetylated highly pure chitin derivatives gave the highest bone volume regeneration of the materials tested.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, there are various evidences on the effectiveness of BE against some types of cancer cells that had gained chemotherapy and radiotherapy resistance [30] and high invasion ability tumor [31], particularly osteosarcoma bone tumor [32] that, in some cases, need to be excised and refilling the loss of bone tissue with suitable synthesized graft. Scientists can take advantage of the promising antioncogenic property of BE with other antiinflammatory and antibacterial features by getting it carried and released in a sustained pattern from nanofibers-based scuffled graft, which would ensure significant reconstructional in segmental bone loss by remodeling and regeneration processes [33][34][35], and in the same time, preventing any probable infectious complications or tumor recurrence in the newly formed tissue and reducing the need of higher dose of chemotherapy by controlling the local environment [36].…”
Section: Limitations and Forward Applicationsmentioning
confidence: 99%